Alpha-synuclein oligomers and fibrils originate in two distinct conformer pools: a small angle X-ray scattering and ensemble optimisation modelling study. Issue 1 (29th October 2014) - Curtain, Cyril C.; Kirby, Nigel M.; Mertens, Haydyn D. T.; Barnham, Kevin J.; Knott, Robert B.; Masters, Colin L.; Cappai, Roberto; Rekas, Agata; Kenche, Vijaya B.; Ryan, Timothy
Abstract : Size exclusion chromatography with small angle X-ray scattering and ensemble optimisation modelling reveals conformers in random pool of α-synuclein. Abstract : The 140 residue intrinsically disordered protein α-synuclein (α-syn) self-associates to form fibrils that are the major constituent of the Lewy body intracellular protein inclusions, and neurotoxic oligomers. Both of these macromolecular structures are associated with a number of neurodegenerative diseases, including Parkinson's disease and dementia with Lewy bodies. Using ensemble optimisation modelling (EOM) and small angle X-ray scattering (SAXS) on a size-exclusion column equipped beamline, we studied how the distribution of structural conformers in α-syn may be influenced by the presence of the familial early-onset mutations A30P, E45K and A53T, by substituting the four methionine residues with alanines and by reaction with copper (Cu 2+ ) or an anti-fibril organic platinum (Pt) complex. We found that the WT had two major conformer groups, representing ensembles of compact and extended structures. The population of the extended group was increased in the more rapidly fibril-forming E45K and A53T mutants, while the compact group was enlarged in the oligomer-forming A30P mutant. Addition of Cu 2+ resulted in the formation of an ensemble of compact conformers, while the anti-fibril agent and alanine substitution substantially reduced the population of extended conformers. Since our observations with the mutants suggest that fibrils may be drawn from the extended conformer ensemble, we propose that the compact and extended ensembles represent the beginning of oligomer and fibril formation pathways respectively, both of which have been reported to lead to a toxic gain of function. Manipulating these pathways and monitoring the results by EOM and SAXS may be useful in the development of anti-Parkinson's disease therapies.